2015
DOI: 10.1061/(asce)co.1943-7862.0001021
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigation of Factors Contributing to the Psychological Safety Climate on Construction Sites

Abstract: Employees' safety climate perceptions dictate their safety behavior, as individuals act based on their perceptions of reality. Extensive empirical research in applied psychology confirmed this relationship. However, rare efforts have been made to investigate the contributing factors to a favorable safety climate in the construction research. As an initial effort to address the knowledge gap, this paper examines contributing factors to psychological safety climate, an operationalization of safety climate at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…= 0.000). It was noted that the threshold value of Cronbach’s alpha is 0.70, which is often acknowledged [ 124 ]. Secondly, reliability analysis can reflect the consistency and stability of results through Cronbach’s alpha, which ranges from 0–1.…”
Section: Discussionmentioning
confidence: 99%
“…= 0.000). It was noted that the threshold value of Cronbach’s alpha is 0.70, which is often acknowledged [ 124 ]. Secondly, reliability analysis can reflect the consistency and stability of results through Cronbach’s alpha, which ranges from 0–1.…”
Section: Discussionmentioning
confidence: 99%
“…First, leaders at different hierarchical levels determine organizational climate, including safety climate. This is because from leaders’ response subordinates recognize which policies, procedures, practices and behaviors would be rewarded or supported [ 8 ]. Second, safety behavior is influenced by an individual’s cultural background.…”
Section: Introductionmentioning
confidence: 99%
“…The sample of this study was mainly the Hong Kong Chinese, who are in a society higher in power distance. In such a society, leadership may have a significant impact on subordinates’ safety climate perceptions [ 8 ]. Therefore, after model modification this study aims to examine the mechanisms through which transformational leadership impacts safety behavior via safety climate.…”
Section: Introductionmentioning
confidence: 99%
“…However, a series of theoretical and empirical studies [12] showed that various factors at the organizational and individual levels play important roles in the decision-making process and those factors can be conflicting. e eory of Planned Behaviour does not harbour the attitudinal ambivalence that is caused by conflicting factors leading to unsafe acts and therefore provides an incomplete picture of the possible relationship between safety attitude and safety behaviour.…”
Section: Introductionmentioning
confidence: 99%